Creativity and educational practices. Towards a model of development of critical and creative skills - Francesca Bracci (Firenze University Press, 2022)
This article proposes a reflection on the development of an educational model to promote creative thinking skills specifically addressed to students who are preparing for teaching professions. The reasons underlying this interest are related to recognizing: (1) creativity, also in light of the development of technologies, as one of the most requested and rewarded skills compared to the professional scenarios that are taking shape; (2) the centrality that future professionals working in school institutions have in forming global citizens who are able to move in a world that is constantly changing, helping to make it more inclusive, socially cohesive, sustainable and productive. A practice-based, cultural, and distributed perspective is adopted to the study of creativity that assumes it both as a social, cultural and contextualized process and as a set of skills implemented through discursive and collaborative constructions of tasks, solutions and innovations within daily interactions.   Creatività e professioni educative. Verso un modello di sviluppo di competenze di pensiero critico e creativo. L'articolo propone una riflessione sullo sviluppo di un modello didattico per promuovere competenze di pensiero creativo specificatamente indirizzato a studenti e studentesse che si preparano alle professioni educative e di insegnamento, iscritti cioè a CdS L-19, LM-85, LM-57, LM-85 bis. Le ragioni sottese a questo interesse sono riconducibili al riconoscere: (1) la creatività, anche alla luce dello sviluppo delle tecnologie, come una delle abilità più richieste e premiate rispetto agli scenari professionali che si vanno configurando; (2) la centralità che futuri professionisti/e operanti nelle istituzioni educative e scolastiche hanno nel formare cittadini/e globali che siano capaci di muoversi in un mondo che cambia continuamente, contribuendo a renderlo più inclusivo, socialmente coeso, sostenibile e produttivo. È adottata una prospettiva practice-based, culturale e distribuita allo studio della creatività che la assume sia come processo sociale, culturale e contestualizzato sia come set di competenze messe in atto attraverso costruzioni discorsive e collaborative di compiti, soluzioni e innovazioni all'interno delle interazioni quotidiane.